2020
DOI: 10.1515/opag-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil plantation and cultivation: Prosperity and productivity of smallholders

Abstract: Indonesia developed the Smallholder Plantation Scheme (PIR) in the early 1980s, making smallholders an important part of the national scale. Increasing smallholder yields is an important instrument for increasing local income and livelihoods. However, small-scale oil palm expansion has problems with low productivity and quality of production. Therefore, to increase their productivity and improve their cultivation, this study measures the importance of planting behavior and specific treatment of farmers’ prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
1
22
1
2
Order By: Relevance
“…Hence, even though it had a significant effect on farming profit, transaction costs would not significantly affect farming capital formation. This study's results are inconsistent with the study of Herdiansyah, Negoro, Rusdayanti, & Shara, (2020), which found that transaction costs significantly affected profit and the farming capital formation in oil palm plantations. It was because farmers worked together or took collective action with the Village Unit Cooperative, which caused large and small transaction costs on profit and farming capital formation.…”
Section: The Effect Of Transaction Costs On the Capital Formation Of Soybean Farmingcontrasting
confidence: 99%
“…Hence, even though it had a significant effect on farming profit, transaction costs would not significantly affect farming capital formation. This study's results are inconsistent with the study of Herdiansyah, Negoro, Rusdayanti, & Shara, (2020), which found that transaction costs significantly affected profit and the farming capital formation in oil palm plantations. It was because farmers worked together or took collective action with the Village Unit Cooperative, which caused large and small transaction costs on profit and farming capital formation.…”
Section: The Effect Of Transaction Costs On the Capital Formation Of Soybean Farmingcontrasting
confidence: 99%
“…In total, 423 functional palm oil processing factories are established in Malaysia (Chiew and Shimada 2013 ). The expansion of oil palm plantation and setting up of large processing companies maximise profit at low cost and minimal labour (Herdiansyah et al 2020 ). These companies are more concerned about high yielding and early maturing oil palm variety seeds (Durand-Gasselin and Cochard 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oil palm is a tropical plant that is thought to have originated from Nigeria (West Africa). Oil palm is an important oil-producing crop in the tropical region that can also be used as a raw material for the food and non-food industries (Herdiansyah et al 2020). On the banks of the Barumun River, the oil palm plantations maintained by the local community are one of the primary resources of livelihood of the community.…”
Section: Species Composition Of Riparian Vegetation In Barumun Watershedmentioning
confidence: 99%